Implementasi Peraturan Daerah Nomor 3 Tahun 2020 Dalam Rangka Sosialisasi Program Pembangunan Irigasi di Desa Mangga Dua - Manik, Dimas (Universitas Muhammadiyah Sumatera Utara, 2023)
This research aims to provide an overview of the Implementation of Regional Regulation Number 3 of 2020 in the Context of Socializing the Irrigation Development Program in Mangga Dua Village. This research method uses a qualitative approach, data collection techniques are carried out through interviews, observation and documentation. The research results show that supervision needs to be carried out in carrying out a program so that the program being implemented runs according to the aims to be achieved. It can be seen that the Mangga Dua Village Government and P3A carry out supervision as a form of responsibility for policies made based on regional regulations number 3 of 2020 concerning irrigation as a form of routine supervision as a form of concern, such as supervision of irrigation development activities and supervision of irrigation networks. There has been a decision made. deliberation meetings and inviting all elements of society to be involved in making policy decisions for the construction of irrigation networks and always calling on the chairman of the P3A in decision making as well as elements of society.